PERBANDINGAN ADMINISTRASI PUBLIK PELAYANAN PUBLIK MANUAL DAN DIGITAL DI DINAS PENANAMAN MODAL TERPADU SATU PINTU KOTA BANJAR - Wardani, Ari Kusumah; Alvin, Muhammad; Rismayanti, Rismayanti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The development of information technology is driving the transformation of public service systems from manual to digital systems to improve the quality of public services. The Banjar City Investment and One-Stop Integrated Services Agency (DPMPTSP), as the agency that administers licensing services, is required to adapt to these changes. This study aims to compare the manual and digital service systems at the DPMPTSP in Banjar City in terms of effectiveness, efficiency, ease of access, transparency, and public satisfaction. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the digital service system has advantages over the manual system, particularly in accelerating the service process, reducing direct face-to-face interactions, increasing data accuracy, and expanding public access to services. However, the manual system still has a specific role, especially for communities with limited digital literacy and technological access. Therefore, an integration strategy and assistance are needed in the implementation of the digital service system so that the transformation of public services at the DPMPTSP in Banjar City can be inclusive, effective, and sustainable.